PENGARUH PEMBUATAN TAKIK REBAH DAN TAKIK BALAS TERHADAP ARAH JATUH POHON: STUDI KASUS DI HUTAN TANAMAN DI PULAU LAUT, KALIMANTAN SELATAN - Asep Hidayat; H Hendalastuti R (Jurnal Penelitian Hasil Hutan, 2004)
Study of the effect of making undercut and back cut on the accuracy of tree felling direction and its effect on stump and technical wastes was conducted in plantation forest of Pulau Laut, South Kalimantan. Sampling trees were chosen purposively to the amount of 52 trees. Data on treefelling direction accuracy and the produced wastes were analyzed descriptively. Results showed that the combination of making either right or wrong undercut, and either right or wrong back cut was not the only factor affecting the accuracy of tree felling direction. It showed also that the quantity of the produced wastes was not only affected by accuracy or deviation on tree felling direction.